2001
DOI: 10.3138/jcfs.32.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Discrepant Parent-Adolescent Views on Family Functioning: Predictors of Poorer Self-Esteem and Problems of Emotion and Behaviour in British and Canadian Adolescents

Abstract: Conflict between a parent and an adolescent may be indicative of problems of family cohesion, and may predict poorer self-esteem and problems of emotion and behavior. This idea is explored in high school and junior college populations in Alberta, Canada, and in Britain. In all, 1,796 12 to 19-year-olds completed the summary scale of the McMaster Family Assessment Device (FAD), which was also completed by a parent. Results were generally similar in both cultures, with many more similarities than differences. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
3
13
2
Order By: Relevance
“…This may relate to parents providing a more global or idealized approach to assessing parenting, whereas the adolescent may report on perceptions stemming from their immediate interactions between themselves and their parent (Bagley, et al, 2001). Other studies have shown that nonconcordance in perceptions between adolescents and their parents may be negatively related to adolescent adjustment, including increased levels of conflict and stress within the family resulting in problem behaviors (Ohannessian, Lerner, Lerner, & Von Eye, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may relate to parents providing a more global or idealized approach to assessing parenting, whereas the adolescent may report on perceptions stemming from their immediate interactions between themselves and their parent (Bagley, et al, 2001). Other studies have shown that nonconcordance in perceptions between adolescents and their parents may be negatively related to adolescent adjustment, including increased levels of conflict and stress within the family resulting in problem behaviors (Ohannessian, Lerner, Lerner, & Von Eye, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In rare instances in the literature when both parents and their children report about parenting behaviors, parents demonstrate a tendency to overestimate (as compared to the child) involvement in their child’s life, especially with regards to monitoring and discipline (Cottrell, et al, 2003; Gonzales, Cauce, & Mason, 1996). In fact, some studies report large differences between parent and adolescent reports of parenting practices (Latendresse, et al, 2009; Pelegrina, et al, 2003; Schwarz, Barton-Henry, & Pruzinsky, 1985), perceptions of family functioning (Bagley, Bertrand, Bolitho, & Mallick, 2001; Villar, Luengo, Gomez-Fraguela, & Romero, 2006), and socialization (Hughes, Hagelskamp, Way, & Foust, 2009). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Child maltreatment is a serious threat to children's physical and psychological well-being (Damashek, Balachova, & Bonner, 2011). Child maltreatment can result in significant longterm emotional and behavioral consequences, including posttraumatic stress disorder (e.g., Dubner & Motta, 1999), aggression and anger (Shields, Cicchetti, & Ryan, 1994;Korkut, 2011;Taner & Gokler, 2004;Chapple, Tyler, & Bersani, 2005), school difficulties (Erickson & Egeland, 2002), depression (Boney-McCoy & Finkelhor, 1996), social difficulties (Mannarino & Cohen, 1996), criminal behavior (Gelles & Straus, 1990), low life satisfaction (Korkut, 2012) and self esteem (Bagley, Bolitho, & Mallick, 2001;Baldry, 2003;Durmuşoğlu & Doğru, 2006;Korkut, 2012) and long-term health problems (Anda et al, 2006). Physical child abuse refers to acts that cause pain and permanent or temporary damage to the child's physical functions, such as bruises, burns, head injuries, fractures, or internal injuries (Kolko, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent perceptions of family functioning have been identified as the mediating variable between family life and adolescent functioning (Powers, Welsh, & Wright, 1994). Further, discrepancies between parent and adolescent perceptions were found to be better predictors of emotional and behavioural disorders than perceptions of parent or adolescent alone (Bagley et al, 2001). This literature emphasises the importance of different perceptions between parents and adolescents, and the importance of such perceptions in relation to mental health.…”
Section: Introductionmentioning
confidence: 99%